Love, Friendship, and Disaffection in Plato and Aristotle: Toward a Pragmatist Analysis of Interpersonal Relationships - Prus, Robert; Camara, Fatima (Qualitative Sociology Review, 2010)
Although much overlooked by social scientists, a considerable amount of the classical Greek literature (circa700-300BCE) revolves around human relationships and, in particular, the matters of friendship, love and disaffection. Providing some of the earliest sustained literature on people's relations with others, the poets Homer (circa 700BCE) and Hesiod (circa 700BCE) not only seem to have stimulated interest in these matters, but also have provided some more implicit, contextual reference points for people embarked on the comparative analysis of human relations. Still, some other Greek authors, most notably including Plato and Aristotle, addressed these topics in explicitly descriptive and pointedly analytical terms. Plato and Aristotle clearly were not of one mind in the ways they approached, or attempted to explain, human relations. Nevertheless, contemporary social scientists may benefit considerably from closer examinations of these sources. Thus, while acknowledging some structuralist theories of attraction (e.g., that similars or opposites attract), the material considered here focus more directly on the problematic, deliberative, enacted, and uneven features of human association. In these respects, Plato and Aristotle may be seen not only to lay the foundations for a pragmatist study of friendship, love, and disaffection, but also to provide some exceptionally valuable materials with which to examine affective relations in more generic, transhistorical terms.